Strategy of Local Television Stations to Maintain Existence Entering the Digital Broadcasting Era - Feri ferdinan alamsyah; Ahsani Taqwim Aminuddin; Desi Amaliah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The implementation of the analog to digital broadcast system migration policy in the broadcasting sector in Indonesia presents certain challenges, especially for local broadcasting industry. Broadcasting experts predict that changes to the broadcast system will have a major impact on the industry, the worst possibility is bankruptcy. Therefore, television station managers need to make a number of effective strategies to make the industry sustainable and remain stable while adapting to the digital broadcast system. This article attempts to explain the strategy of local television stations in adapting to digital broadcast systems. Data was obtained through a qualitative tradition that focuses on in-depth observation. To see the strategic tendencies of local television stations, the SWOT analysis method is used. The subject of this article is a television station broadcasting in West Java, Indonesia, then selected purposively using a number of criteria, namely MGSTV, SMTV, and MQTV. The research results show that the strategy of local television stations in adapting to digital broadcast technology emerged on the basis of two big goals, namely the short term and the long term. In the short term, local television stations have a target to survive, and long term strategies aim to develop.